Manual handling as risk factor of low back pain among workers - Harrianto, Ridwan; Samara, Diana; Tjhin, Purnamawati; Wartono, Magdalena (Universa Medicina, 2009)
Disorders of the musculoskeletal system constitute a considerable health problem in industrialized societies. Low back pain (LBP) remains a common and costly problem among the workers. Workplace injuries, primarily musculoskeletal disorders, are a persistent problem for nursing. A cross-sectional study was conducted to investigate prevalence of LBP as well as the potential risk factors associated with LBP. These potential risk factors include individual characteristics, job duration, type of work, and manual handling knowledge and practice. Seventy-six subjects consisting of 30 nurses and 46 administrative workers were recruited into the study. Symptoms of LBP cases were assessed by means of a simple questionnaire, and the diagnosis of LBP was confirmed by clinical examination. The study showed that the overall point prevalence rate of LBP was 42.1%, while the overall 12-month prevalence rate was 69.7%. Occupational group and manual handling practice were independent predictors for point prevalence of LBP. Nursing occupation significantly increased the risk of point prevalence rate of LBP by 2.703 (95% C.I. OR 1.046 â 6.984) compared to administrative workers. Nurses with frequent manual handling practice had a 2.917-fold higher risk of developing a point prevalence of LBP, although this risk was statistically not significant (OR=2.917;95% C.I. 0.094-3.003). The study indicates that an association exists between manual handling practice and LBP prevalence.